Power and Paranoia in the Age of Pornhub. - Holt, Becky (Discourse: Journal for Theoretical Studies in Media & Culture)
This article provides an overview of the popular online pornography platform, Pornhub, and its impact on various aspects of society. It explores the company's history, corporate structure, and the controversies surrounding it, such as piracy, exploitation, and hosting illegal content. The article also discusses the perception of pornography in the digital age and its influence on the internet and society. It emphasizes the need for further research and a nuanced understanding of the industry and its complexities.